Early versus late decompressive craniectomy in traumatic brain injury: A retrospective comparative case study. (April 2021) - Fatima, Nida; Mujeeb-Ur-Rehman,; Shaukat, Samia; Shuaib, Ashfaq; Raza, Ali; Ayyad, Ali; Saqqur, Maher
Objectives: Decompressive craniectomy is a last-tier therapy in the treatment of raised intracranial pressure after traumatic brain injury. We report the association of demographic, radiographic, and injury characteristics with outcome parameters in early (<24 h) and late (≥24 h) decompressive craniectomy following traumatic brain injury. Methods: We retrospectively identified 204 patients (158 (early decompressive craniectomy) and 46 (late decompressive craniectomy)), with a median age of 34 years (range 2–78 years) between 2015 and 2018. The primary endpoint was Glasgow Outcome Scale Extended (GOSE) at 60 days, while secondary endpoints included Glasgow Coma Score (GCS) at discharge, mortality at 30 days, and length of hospital stay. Regression analysis was used to assess the independent predictive variables of functional outcome. Results: With a clinical follow-up of 60 days, the good functional outcome (GOSE = 5–8) was 73.5% versus 74.1% (p = 0.75) in early and late decompressive craniectomy, respectively. GCS ≥ 9 at discharge was 82.2% versus 91.3% (p = 0.21), mortality at 30 days was 10.8% versus 8.7% (p = 0.39), and length of stay in the hospital was 21 days versus 28 days (p = 0.20), respectively, in early and late decompressive craniectomy groups. Univariate analysis identified that GCS at admission (0.07 (0.32–0.18; < 0.05)) and indication for decompressive craniectomy (3.7 (1.3–11.01; 0.01)) are significantly associated with good functional outcome. Multivariate regression analysis revealed that GCS at admission (<9/≥9) (0.07 (0.03–0.16; <0.05)) and indication for decompressive craniectomy (extradural alone/ other hematoma) (1.75 (1.09–3.25; 0.02)) were significant independent predictors of good functional outcome irrespective of the timing of surgery. Conclusions: Our results corroborate that the timing of surgery does not affect the outcome parameters. Furthermore, GCS ≥ 9 and/or extra dural hematoma are associated with relatively good clinical outcome after decompressive craniectomy.